2011
DOI: 10.1177/1352458511410515
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus nuclear antigen-1 B-cell epitopes in multiple sclerosis twins

Abstract: In a study that controls for confounders, our data focus an EBNA-1 specificity that may be associated with MS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Among the observations that remained unexplained are the change in risk among migrants (Gale and Martyn 1995), a probable MS outbreak in the Faroe islands (Kurtzke and Heltberg 2001), and the increasing MS frequency among African-Americans in the USA (Wallin et al 2012) and among women in several countries in North America (Orton et al 2006) and Europe (Koch-Henriksen and Sorensen 2010). One possibility is that there are genetic variations in EBV itself that modulate its propensity to cause MS. A few reports have addressed this hypothesis (Munch et al 1998;Lindsey et al 2008;Mechelli et al 2011) as well as interactions with genetic or environmental factors, which could include other infectious agents.…”
Section: Summary On Ebv and Msmentioning
confidence: 98%
“…Among the observations that remained unexplained are the change in risk among migrants (Gale and Martyn 1995), a probable MS outbreak in the Faroe islands (Kurtzke and Heltberg 2001), and the increasing MS frequency among African-Americans in the USA (Wallin et al 2012) and among women in several countries in North America (Orton et al 2006) and Europe (Koch-Henriksen and Sorensen 2010). One possibility is that there are genetic variations in EBV itself that modulate its propensity to cause MS. A few reports have addressed this hypothesis (Munch et al 1998;Lindsey et al 2008;Mechelli et al 2011) as well as interactions with genetic or environmental factors, which could include other infectious agents.…”
Section: Summary On Ebv and Msmentioning
confidence: 98%
“…In MS, the strongest disease association has been demonstrated to a C-terminal EBNA-1 domain comprising amino acids (aa) 385–420 [40,41]. In a recent study including nine MS-discordant monozygotic twins, this was further narrowed down to aa 401–411, revealing increased response against this epitope in affected compared to healthy co-twins [42]. Lünemann and colleagues have demonstrated that children with MS have a broader IgG response against all three domains of the EBNA-1 protein and that some of the responses against the glycine-alanine repeat domain (aa 88–323) are directed against epitopes not found in the sera of demographically matched healthy peers [43].…”
Section: Evidence Of Associationmentioning
confidence: 99%
“…The GA-rich region has been described as the primary target of the normal peripheral humoral immune response (92)(93)(94)(95)97). This is verified by our data.…”
Section: Cryab: Igg Binding the N-terminal Region Maymentioning
confidence: 99%